Respuesta :
Answer:
a = -1
and a ≠ -3 , 3
Step-by-step explanation:
Given Equation :
[tex]\frac{a}{a+3}=\frac{2a}{a-3}-1[/tex]
We need to solve the given equation.
Clearly given equation has 2 rational terms.
We know that Denominator of rational Numbers can not be equal to 0.
So, a + 3 ≠ 0 ⇒ a ≠ - 3 and a - 3 ≠ 0 ⇒ a ≠ + 3
⇒ a can not be equal to 3 and -3.
Now Consider,
[tex]\frac{a}{a+3}=\frac{2a}{a-3}-1[/tex]
[tex]\frac{a}{a+3}=\frac{2a-(a-3)}{a-3}[/tex]
[tex]\frac{a}{a+3}=\frac{2a-a+3}{a-3}[/tex]
[tex]\frac{a}{a+3}=\frac{a+3}{a-3}[/tex]
[tex]a(a-3)=(a+3)(a+3)[/tex]
[tex]a^2-3a=a^2+2(a)(3)+(3)^2[/tex]
[tex]a^2-3a=a^2+6a+9[/tex]
[tex]6a+3a=-9[/tex]
[tex]9a=-9[/tex]
[tex]a=-1[/tex]
Therefore, a = -1